Species traits explaining long-term abundance changes of breeding birds in farmland areas in Álava (N Spain) - José Antonio Gainzarain; Gorka Belamendia (Munibe Ciencias Naturales)
In recent decades, the populations of many common bird species have greatly declined in Europe, particularly in farmland habitats. However, this decline has not affected every species, and to understand the mechanisms behind this interspecific variability, its relationship with several species-specific traits has been studied repeatedly. We used this approach to analyse long-term changes in the abundance of breeding passerines in farmland areas in northern Spain. Abundance changes were quantified in 2015 and 2016 by repeating the same line transects conducted in 1988/89 in three agricultural habitats located along a steep Atlantic-Mediterranean gradient in the province of Álava. We found that total bird abundance did not decline, as most species not closely linked to farmland habitats showed positive population changes, while the number of increasing and decreasing farmland specialists was similar. Specific traits explained a substantial proportion of the variability in abundance change, as warm-dwelling species and those occupying habitats with a complex vegetation structure showed more positive changes than those preferring colder conditions and more open habitats. These patterns can be explained by climate warming and by the increase in hedge and forest cover in the study area. Although we did not find a long-term decline in the overall abundance of the studied bird community nor in that of farmland specialists, open habitat species associated with a cool climate should be the focus of particular concern. RESUMEN : Los rasgos de las especies explican los cambios a largo plazo en la abundancia de aves nidificantes en medios agrícolas en Álava (Norte de España). Muchas especies de aves comunes en Europa han experimentado acusados descensos poblacionales en las últimas décadas, especialmente en medios agrícolas. Sin embargo, este declive no ha afectado a todas las especies, y para comprender los mecanismos que subyacen tras esta variabilidad interespecífica, se ha estudiado repetidamente su relación con diversos rasgos ecológicos propios de cada especie. En este estudio utilizamos este enfoque para analizar los cambios a largo plazo en la abundancia de los passeriformes nidificantes en áreas agrícolas del norte de España. Los cambios en la abundancia se cuantificaron repitiendo en 2015 y 2016 los mismos transectos realizados en 1988/89 en tres hábitats agrícolas situados a lo largo de un pronunciado gradiente Atlántico-Mediterráneo en la provincia de Álava. No se observó una reducción en el número total de aves, ya que la mayoría de las especies no asociadas estrechamente con medios agrícolas aumentaron su abundancia, mientras que el número de especialistas agrícolas que mostraron declives poblacionales fue similar al de aquellos que aumentaron. Los rasgos específicos explicaron una proporción sustancial de la variabilidad en los cambios de abundancia, ya que las especies propias de climas cálidos y las que ocupan medios con una estructura vegetal compleja mostraron cambios más positivos que las asociadas a temperaturas más frías y a hábitats más abiertos. Estos patrones se pueden explicar por los efectos del calentamiento global y del incremento en la cobertura de setos y bosques en el área de estudio. Aunque no se registró un declive a largo plazo en la abundancia total de las comunidades de aves estudiadas ni en la de especialistas agrícolas, las especies de espacios abiertos asociadas a climas fríos deberían ser objeto de especial atención.